Congenital dysprothrombinemia: an inherited structural disorder of human prothrombin - Shapiro, Sandor S. (1969)
A large family has been studied, 11 of whose members have half-normal plasma concentrations of biological prothrombin activity. The pattern of inheritance is autosomal. By use of a specific immunoassay, affected family members have been shown to possess normal quantities of immunoreactive prothrombin, whose immunologic properties seem identical with those of the normal zymogen. Prothrombin isolation from the plasma of one such individual gave normal yields of protein but half-normal amounts of prothrombin activity. Activation of this material in the “intrinsic” and “extrinsic” systems, in concentrated sodium citrate, or by trypsin, gives rise to half, or less, of the thrombin clotting and esterase activities expected from a comparable normal prothrombin preparation. During the clotting of blood from an affected individual, all material with the mobility of prothrombin disappears. Immunoelectrophoresis of the serum reveals a normal nonthrombin “pro piece,” and an additional activation product with an electrophoretic mobility intermediate between that of prothrombin and of “pro piece.” These results suggest that affected individuals are heterozygotes in whom half the prothrombin molecules synthesized are structurally abnormal, since they undergo some alterations during activation, but are incapable of releasing the active enzyme, thrombin.